Evaluasi Pengaruh Tata Ruang Bioskop Empire Xxi Terhadap Kenyamanan Dan Kesehatan Pengguna - Akmal, Fathuddin (Journal of Comprehensive Science, 2025)
The Covid-19 pandemic has changed people's perspectives and responses to many things. Health protocols have emerged that must be adhered to and implemented in all public facilities, restaurants, hospitals, and cinemas, including cinemas. Cinemas are a popular public facility for all groups, therefore, health issues in cinemas must also be considered. During this pandemic, architects must pay closer attention to the layout of cinemas, which are close to human density to prevent the spread of the Covid-19 virus and prevent its transmission. Cinemas are places where visitors gather together and spend extended periods of time, around 1-2 hours. Comfort is the most important aspect when designing cinema spaces. Comfort, which is the benchmark and the goal, is also related to health. Health visitors here are not only concerned with the spread of Covid-19, but also discuss issues of eye health, bone health, and others. The Empire XXI Cinema in Yogyakarta is the object of research that examines aspects of comfort and health in architecture. The case study in this research is the film screening room at the Empire XXI Cinema Yogyakarta. This study aims to determine whether this cinema screening room is considered comfortable for its users. It also examines its architectural design to determine its level of comfort and its impact on user health.